(Introduction) Expats: places/spaces/baggage - Gatley, J; Douglas, C (Auckland, NZ: Enigma, 2008)
In 2005, the New Zealand Institute of Architects (NZIA) celebrated its centenary and convened a conference titled Taking Stock, which featured as keynote speakers a series of New Zealand-educated architects who practise overseas. The conference sought to gain a perspective on New Zealand architecture from expatriate eyes. In the same vein, another expat New Zealander, Helene Furján, now working at the University of Pennsylvania, suggested the expat theme for Interstices 09.
Keywords: Architecture; Globalisation